The Challenge of Deep Ocean Drilling for Natural Gas Hydrate - Spence, George; Hyndman, Roy (Geoscience Canada, 2001)
Summary Large reservoirs of natural gas hydrate have been sampled extensively by past DSDP, ODP, and other scientific oceandrilling. Gas hydrate is an ice-like solid consisting of gas molecules, commonly methane, trapped in a cage of watermolecules. Global estimates of the methane content of natural gas hydrate are very large, potentially enormous. Such large quantities of gas hydrate could be important as a clean energy source, as a controlin global climate, and as a factor in seafloor slumps and slides. Gas hydrateoccurs only in water depths greater than about 600 m at temperate latitudes, but occurs on land and in shallow water in the Arctic. The formation mechanisms of gas hydrates are only partly understood. Gas hydrate appears to be formed usually by migrating fluids carrying biologically generated methane upward to regions ofsufficiently low temperature and high pressure where the hydrate is stable.Quantitative aspects of this formation model need testing, however, and questions remain about the sources and sinks for methane, and the amount that can reach die atmosphere. In Canada, gashydrates are found on most of its conti-nental margins, notably on the continental slope off Vancouver Island and in the Mackenzie Del ta-Beaufort Sea region. A drilling program off Vancouver Island would examine gas hydrates in a well-studied accretionary sedimentary wedge; such sediments appear to be the most common environment in which hydrates are found globally. Drilling for gas hydrate offshore in the Canadian Arctic, perhapsusing an alternative drilling platform, would complement a current onshore Arctic gas hydrate drilling program in the permafrost environment. The Arctic landand shallow sea hydrate are important because such hydrate is especially susceptible to global climate change.